The clinical and immunological profiles of systemic lupus erythematosus patients from Assam, North-East India - Debashree Talukdar; Akash Protim Gogoi; Daisy Doley; Rebecca R Marak; Sanjeeb Kakati; Vandana Pradhan; Anita H Nadkarni; Shashi Baruah (Indian Journal of Rheumatology, 2020)
Objective: The objective of this study is to document the clinical and immunological profiles of systemic lupus erythematosus (SLE) patients from the Upper Assam region and to evaluate the relevance of autoantibody combinations on the clinical presentation of SLE. Materials and Methods: One hundred and forty-five SLE patients were enrolled in the study. Anti-nuclear antibody (ANA) profiles and titers of autoantibodies were determined using the ANA blot and enzyme-linked immunosorbent assay, respectively. The patients were clustered based on autoantibody titers and clinical features among the clusters were compared. Results: Mucocutaneous (87.59%), hematological (69.65%), renal (58.03%), and musculoskeletal (50.34%) manifestations were the common clinical complications, whereas anti-double stranded deoxyribonucleic acid (dsDNA) antibody was noted in 62.76% of the patients. Patient clustering using autoantibody titers revealed that the cluster with a combination of high titers of anti-dsDNA, anti-nucleosome (Nuc), and anti-ribosomal P (Rib-P) antibody had complex disease presentation with higher frequencies of oral/nasal ulcer, serositis, musculoskeletal, hematological, and central nervous system manifestations. Conclusion: The most common clinical features of the SLE patients were mucocutaneous, hematological, renal and musculoskeletal manifestations, and anti-dsDNA antibody was the most frequent autoantibody. A combination of high titers of anti-dsDNA, anti-Nuc, and anti-Rib-P antibodies showed association with disease complexity but not the combinations of autoantibodies against extractable nuclear antigens.